Advances in the Management of Low-Density Lipoprotein Cholesterol - Parry, Nicola (MD Conference Express, 2015)
This article highlights select advances in the intensive management of low-density lipoprotein cholesterol levels. It discusses the use of statins as the cornerstone of treatment, addresses the use of novel adjuvant therapies for reducing atherogenic lipoproteins, and highlights data from important new studies demonstrating the safety and clinical impact of much more aggressive low-density lipoprotein cholesterol reduction in patients with established coronary artery disease.